2013
DOI: 10.1098/rstb.2012.0154
|View full text |Cite
|
Sign up to set email alerts
|

The fate of phosphorus fertilizer in Amazon soya bean fields

Abstract: Fertilizer-intensive soya bean agriculture has recently expanded in southeastern Amazonia, and whereas intensive fertilizer use in the temperate zone has led to widespread eutrophication of freshwater ecosystems, the effects in tropical systems are less well understood. We examined the fate of fertilizer phosphorus (P) by comparing P forms and budgets across a chronosequence of soya bean fields (converted to soya beans between 2003 and 2008) and forests on an 800 km 2 soya bean farm in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 45 publications
(88 reference statements)
5
58
0
4
Order By: Relevance
“…Original forest clearing at Fazenda Tanguro occurred in the early 1980s and land was used for cattle pasture for ;20 years until conversion to soybean cultivation from 2003 to 2008 (Riskin et al 2013). It is possible that changes to forest structure took place closer to the time of initial land clearing, but that over time these effects have lessened as altered riparian forest edges fill in, as has occurred in some forest fragments Lawton 1999, Laurance et al 2002; but see Laurance et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Original forest clearing at Fazenda Tanguro occurred in the early 1980s and land was used for cattle pasture for ;20 years until conversion to soybean cultivation from 2003 to 2008 (Riskin et al 2013). It is possible that changes to forest structure took place closer to the time of initial land clearing, but that over time these effects have lessened as altered riparian forest edges fill in, as has occurred in some forest fragments Lawton 1999, Laurance et al 2002; but see Laurance et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Impoundments were also constructed on headwater streams throughout the region to provide water for cattle (Macedo et al 2013). To initiate soybean cultivation beginning in 2003, remaining woody vegetation was piled into rows and burned and the soil was tilled, after which soybeans were planted and maintained using no-till practices (Riskin et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Hawaiian forests have been shown to be dependent on atmospheric inputs of base cations [154], and alpine forests in Europe derive substantial portions of their base-cation subsidies for growth from dust [155]. Recent studies have shown substantial perturbations to atmospheric phosphorus in the Amazon due to deforestationrelated biomass burning [19] and land use [156] suggesting that anthropogenic phosphorus deposition in the Amazon may be enhancing productivity (i.e., net primary production) in the remaining forests, by between 0 and 0.5 PgC/year [10]. Modeling studies of the influence of phosphorus deposition onto carbon uptake are in the beginning stages [157,158]; based on ecosystem budgets, they suggest a smaller role for phosphorus deposition than for nitrogen deposition [157,158].…”
Section: Terrestrial Ecosystemsmentioning
confidence: 99%
“…Durigan et al [23] Macedo et al [24] Neill et al [27] Gardner et al [42] Le Tourneau et al [41] VanWey et al [29] Schwartzman et al [34] Riskin et al [28] Stickler et al [18] Nepstad et al [47] Galford et al [30] Schiesari et al [31] Morton et al [32] Silvério et al [36] Stickler et al [18] DeFries et al [49] Schwartzman et al [34] infrastructure Nepstad et al [47] Macedo et al [24] Neill et al [27] [35] Figure 1. Schematic diagram showing the interconnections among the processes that affect land cover and land-use change (LCLUC) and the social and biophysical outcomes of LCLUC in the Brazilian Amazon.…”
Section: Land-use Change In Mato Grossomentioning
confidence: 99%